2017
DOI: 10.7150/jbm.18877
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Design Strategies for Effective Cancer Immunotherapy

Abstract: Cancer immunotherapy is a rapidly evolving and paradigm shifting treatment modality that adds a strong tool to the collective cancer treatment arsenal. It can be effective even for late stage diagnoses and has already received clinical approval. Tumors are known to not only avoid immune surveillance but also exploit the immune system to continue local tumor growth and metastasis. Because of this, most immunotherapies, particularly those directed against solid cancers, have thus far only benefited a small minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Leuschner et al have shown that delivery of siRNA that targets CCR2-expressing monocytes could abrogate inflammatory responses in atherosclerotic plaques (41). Others have also demonstrated that PLGA NPs deliver tumor-specific antigens to DCs in a protected and sustained-release manner (43)(44)(45). In this study, we demonstrated that the delivery of anti-PD-1 within PLGA NPs facilitated its uptake by DCs and enhanced the effector T cell response in the SLTs.…”
Section: Discussionsupporting
confidence: 57%
“…Leuschner et al have shown that delivery of siRNA that targets CCR2-expressing monocytes could abrogate inflammatory responses in atherosclerotic plaques (41). Others have also demonstrated that PLGA NPs deliver tumor-specific antigens to DCs in a protected and sustained-release manner (43)(44)(45). In this study, we demonstrated that the delivery of anti-PD-1 within PLGA NPs facilitated its uptake by DCs and enhanced the effector T cell response in the SLTs.…”
Section: Discussionsupporting
confidence: 57%
“…In a clinical setting, non-viral based therapeutic miRNAs may be favoured due to their stable composition, lower immunogenicity and ease of manufacturing [ 23 ]. Delivery mechanisms utilising nanoparticles, polymers and liposomes for mediated drug delivery have also been favoured in recent studies [ 167 , 168 ]. However, these applications require further optimisation before miRNAs can become embedded in standard cancer therapeutic development [ 169 ].…”
Section: Overcoming Limitations Of Mirna Biomarkers and Therapeutimentioning
confidence: 99%
“…Cancer immunotherapy is an interesting field in which the nanotechnology can afford different solutions [69]. It has been demonstrated that, in specific cases, nanoparticles can potentially stimulate tumor microenvironments to produce antitumor immunity.…”
Section: Platinum-based Ncpsmentioning
confidence: 99%